(untitled) (Journal of Pathology of Nepal, 2019)
Background: Enteric fever is one of the most common systemic infections of developing countries like Nepal. The changing trend of antibiotic susceptibility and the increasing rate of resistance to the commonly used antibiotics has been of great concern in the proper treatment and prevention of this disease. This study aims to investigate the current antibiotic susceptibility pattern of Salmonella typhi and paratyphi. Materials and Methods: This study was carried out at Patan hospital of Lalitpur, Nepal over a period of Eight months. Blood culture samples were collected from suspected patients presenting to different departments of the hospital and tested microbiologically by standard procedure. Antibiotic susceptibility test was performed by Kirby Bauer Disc Diffusion method and results were interpreted by National Committee for Clinical Laboratory (NCCLS) guidelines. Results: 130 blood culture samples were isolated as Salmonella species. Out of these, 103 (79.2%) cases were S typhi and 27 (20.8%) were S paratyphi A. Isolates were mainly from adult age group. Regarding the antibiotic susceptibility pattern, the sensitivity to Ciprofloxacin and Ofloxacin were 5.4% each whereas the sensitivity to Chloramphenicol, Cotrimoxazole, Gentamycin and Azithromycin were 100%. Nalidixic Acid Resistance Salmonella typhi strains were 87.7%. Conclusions: A high degree of variability is seen in antimicrobial sensitivity pattern with very high degree of sensitivity to the historically used antibiotics like Chloramphenicol and Cotrimoxazole. Sensitivity to quinolones was seen to be very low, which were used widely in the last two decades.